Iodometric Determination Of The Vitamin C Contents Of Selected Citrus Fruits Sold In Lafia Metropolis (FULAFIA IAC Book of Proceedings, 2024)
This study aimed at determination of vitamin C content of five citrus fruits sold in Lafia metropolis using iodometric method of titration. Vitamin C concentrations of the juices and fibers from the five citrus fruits were compared. The results obtained indicated that orange juice had the highest vitamin C concentration of 53.5 mg/100L followed by grapefruit (51.30 mg/100L), lemon (36.3mg/100L), tangerine (30.40 mg/100L) and lime (24.70 mg/100L). Similar trend was also followed in the vitamin C contents of citrus fruit fibers with the order: orange (2.80 mg/10g) > grapefruit (2.60 mg/10g) > lemon (1.00 mg/10g) > tangerine (0.70 mg/10g) > lime (0.20 mg/10g). The results clearly showed that the juice of studied citrus fruits had higher contents of vitamin C than their fibers. The orange is highly rich in vitamin C content followed by grapefruit while lime was of the lowest concentration in both the juice and fiber. Lemon and tangerine had moderate concentrations of vitamin C in both their juices and fibers. This analysis provides essential insights into the nutritional variability of the different citrus fruits, aiding consumers in making informed dietary decision and potentially offering valuable information for the food industry.
Keywords: Vitamin C; Citrus fruits; Iodometric titration; Lafia metropolis